ASPECTS OF POPULATION EVOLUTION IN THE METROPOLITAN AREA OF BRAȘOV DURING THE POST-COMMUNIST PERIOD 1992-2011 - Oana LUPOIU (Studia Universitatis Babeş-Bolyai: Geographia, 2015)
Aspects of Population Evolution in the Metropolitan Area of Brașov During the Post-Communist Period 1992-2011. The metropolitan area of Brașov is an important polarizing center in Transylvania. Throughout the years this metropolitan area suffered not only the territorial, industrial, economic, political transformation but also demographic transformation due to the changes in the demographic structure of population. In this order, first of all we focus on demographic structures and population dynamics emphasizing actual social phenomena such as migration and population ageing. Our study reveals the existence of a similar framework at the national level: migration and ageing of population process. Secondly, we analyze the demographic structure of population in the post-communist period between 1992-2011 emphasizing the evolution of population by age and sector of activity. In our approach we will build a theoretical framework by using statistical data to indicate the demographic tendency of the population in the metropolitan area of Brașov. In the third place we consider the possibility to revitalize the studied area by proposing a few necessary measures for development and change in the mentality of the inhabitants.